Hydrothermal synthesis and characteristics of lanthanumdoped Pb(Zr₀.₆₅Ti ₀.₃₅)O₃ ceramics - Nguyen, Thanh Thuy; Nguyen, Van Tung; Nguyen, Trong Hung; Cao, Duy Minh (Nuclear Science and Technology, 2019)
Lanthanum-doped lead zirconate titanate (PLZT) powders were synthesized using the hydrothermal method. The influence of pH, reaction temperature and time, lanthanum concentration on the formation and characteristics of PLZT were investigated. Obtained powders were investigated using X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) techniques and a dielectric analyzer. The results showed that Pb1-xLax(Zr0.65Ti0.35)O3 with x= 0.0 – 0.1 were well formed under conditions: pH≥13, reaction time of 12hrs, reaction temperature of 180oC. Dielectric constant of PLZT is higher than PZT. The grain size of the PLZT is found to be 1–3.5 µm.